Structuration des bassins de provence orientale a la fin de l'ere primaire. - Bonijoly, D.; Toutin-morin, N. (Cuadernos de Geología Ibérica, 1992)
In Eastem Provenee, tite ultimate pitases of E-W tigittening of the Hercynian tectonies haveproduced, intite Maures andTanneron basement, various defonnations during tite Namurian and tite Westpitalian times (N-S sub-isoclinal folds, ductile deformation along N-S faults). Tite first sedimentaz-y deposits took place at tite end of tite Carboniferous, during the Westphalian and tite Stephanian. Continental basins, often witit flora and volcanie products, developed in a Late-orogenie cornpressive context, along tite great N-S faults already appeared in the basement; they are folded in N-S synclines, at tite end of tite Stephanian. At tite beginning of tite Permian times, tite directions of stress turned and small WNW-ESE basins break down. Tite formations, imputed [o tite Autunian, are tilted and covered, with angularunconformity,by basaLbrecciaof ffie «Saxono-Tituringian». Tite N-S distensional conditions generalized during tite Upper Permian; at tite same time, alkaline volcanicity increased. The activity of tite N-S faults was progress¡vely supplanted by E-W faults which are later. Those two main ortitogonal directions led to tite installation of itigh zones witicit divided tite basins and were movable during the most part of the Permian. Their movement controlled tite fzlling basins: eones of coarse material on (he edge, fine grained sedimentation in the cerner. During tite Upper Permian, tite continental basins funetioned witit distensional conditions whicit annonnee tite Triassic rifting.